Vertical profiles of the stratospheric aerosol extinction coefficient from OMPS-LP limb-scatter measurements V2.1 (single profiles), 2012-2024 - Rozanov, Alexei (PANGAEA, 2025)
The data set contains single vertical profiles (Level 2 data) of the stratospheric aerosol extinction coefficient at a wavelength of 868.6 nm retrieved from the limb-scatter measurements made by the Ozone Mapper and Profiler Suite - Limb Profiler (OMPS-LP) instrument on the joint NASA/NOAA Suomi National Polar-orbiting Partnership (SNPP) satellite mission. The data set contains V2.1 retrieval results and covers 2012-2024 period. The data were retrieved at the Institute of Environmental Physics (IUP) at the University of Bremen using the algorithm described by Rozanov et al. (2024). The vertical coverage of the profiles is 8.5 - 49.5 km, vertical sampling 1 km and vertical resolution is 2-3 km.
Keywords: extinction coefficient; limb-scatter measurements; OMPS-LP; stratospheric aerosol; vertical profiles